PERSEPSI MASYARAKAT TENTANG HUTAN TANAM INDUSTRI (HTI) MILIK PT RIAU ANDALAN PULP AND PAPER (RAPP) DI DESA LUKIT KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI RIAU - Wan Wirna Juwita; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to: 1) determine the community's perception of HTI based on the background aspect 2) determine the community's aspect of HTI based on the environmental aspect 3) determine the community's perception of HTI based on the aspect of community interaction with PT Riau Andalan Pulp and Paper (RAPP). The data analysis technique used is the Mixed Method, which is a method that combines quantitative and qualitative approaches. The research was conducted in Lukit Village, Merbau District, Meranti Islands Regency. The sample of respondents is 85 people, the type of data used is primary data and secondary data. The data collection of this research was carried out by distributing a Liker Scale questionnaire model that had been tested for validation and reliability. The results of the study 1) community perceptions based on land background aspects on land status indicators agree (54%), neutral compensation indicators (59%), forest indicators agree (74%), 2) perceptions based on environmental aspects on damage indicators agree (56%), sustainability indicators disagree (78%), 3) community perceptions based on community involvement aspects based on neutral employment indicators (46%), education assistance indicators agree (54%), decision-making indicators agree (66%). Keywords: Perception, Industrial Plantation Forest (HTI),Society.